The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.9734/jpri/2018/v25i430104
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxins Nebulization over Intravenous Injection: Pharmacokinetics and Pharmacodynamics-Based Therapeutic Evaluation

Abstract: Polymyxins are the last line potential antibiotics against multi-drug resistant gram-negative bacteria and consist of two sister antibiotics: Polymyxin B and colistin (polymyxin E). Intravenous use of polymyxins was started from a long ago in the treatment of serious gram-negative infections and once their uses were restricted due to potential adverse drug reactions, such as nephrotoxicity and neurotoxicity. Lack of in vivo clinical studies on polymyxins mostly, in human body makes the pharmacokinetics and pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…3,12 This increasing trend of resistant organisms causes more infectionassociated hospitalization, treatment failure, mortality and treatment cost. 8,13 In this study, the sensitivity patterns of meropenem, amikacin, ceftazidime and cefepime were significantly lower (all were found below 50% of the sensitivity level) than last resort polymyxin B and colistin to A. baumannii in every selected year. Both polymyxin B and colistin are under the polymyxins group and this is considered as one of the last resort antibiotic groups, globally.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…3,12 This increasing trend of resistant organisms causes more infectionassociated hospitalization, treatment failure, mortality and treatment cost. 8,13 In this study, the sensitivity patterns of meropenem, amikacin, ceftazidime and cefepime were significantly lower (all were found below 50% of the sensitivity level) than last resort polymyxin B and colistin to A. baumannii in every selected year. Both polymyxin B and colistin are under the polymyxins group and this is considered as one of the last resort antibiotic groups, globally.…”
Section: Discussionmentioning
confidence: 56%
“…Both polymyxin B and colistin are under the polymyxins group and this is considered as one of the last resort antibiotic groups, globally. 8 Tigecycline is another last resort antibiotic 14 but, the use of tigecycline is very limited by the prescribers with limited sensitivity data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that a relatively high polymyxin B concentration is significantly achieved in lungs’ sub-compartments after its direct aerosolised administration, and exhibits better microbial eradication compared to intravenous polymyxin B. Conversely, a single-route intravenous administration of polymyxin B in the treatment of severe pneumonia in high-risk ventilated patients of this study, was found to be less efficient in achieving microbial eradication [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 71%
“…To date, in-vivo data are limited regarding the pharmacokinetics of polymyxins in lung tissue after its intravenous or aerosolized administration and the susceptibility of PDR KP strains to polymyxins at differential drug-concentration in the lung tissue. Moreover, the paucity of data on polymyxins’ dose-mediated toxicity in patients with VAP develops conflicts regarding therapeutic modification [ 12 , 13 ]. The optimized therapeutic armamentarium with the last-hope polymyxins may be effective against the PDRKP strains causing VAP.…”
Section: Introductionmentioning
confidence: 99%